Skills of oral communication level among fourth grade students in science - An empirical study conducted in the first cycle schools of basic education in Lattakia city - زمرد, أميرة; سلطان, منال; سمير جمل, محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Aim of the study to determine the skills of oral communication level among fourth grade students, (listening and speaking), The researcher followed the descriptive approach, and the study sample consisted of (670) male and female fourth grade students of Lattakia city schools for the year 2019/2020 , To achieve the study goals, the oral communication skills performance test was applied to the participants, it included (17) questions. Its credibility has been verified from the faculty of education at Tishreen and Damascus Universities, its stability confirmed by applying it to an, using (Cronbach Alpha test), and the stability factor as a whole was (0.845), and through the consistency of repeat was (0.976). The search showed the following results: Fourth graders students have a good level of oral communication skills. Fourth graders students have a good level of listening skill. Fourth graders students have a bad level of speaking skill. There are no statistically significant differences between the mean scores of participants related to speaking skill according to the gender variable, There are statistically significant differences between the mean scores of participants related to listening skill according to the gender variable, and these differences came in favor of females.